EVALUATION OF HEALTH FUNCTION OF SPICES BY GLOBAL COOPERATION INDONESIA AND JAPAN - Sugahara, Takuya (PROCEEDING ICTESS (Internasional Conference on Technology, Education and Social Sciences), 2020)
-